Purification and Properties of the Cathepsin D Type Proteinase from Beef and Rabbit Lung and Its Identification in Macrophages - Rojas-Espinosa, Oscar (1973)
The acid-acting proteinase, cathepsin D (EC 3.4.4.23), was purified from extracts of homogenized rabbit lung and beef lung by autolysis at acid pH, acetone and ammonium sulfate fractionation, column chromatography, and isoelectric focusing. Four isoenzymes were obtained from each source. With acid hemoglobin as the substrate, the proteinase from rabbit lung had a pH optimum of 3.0 and that from beef lung had a pH optimum of 3.6. Their activity was not affected by thiol reagents or by Fe(2+), Mn(2+), or Mg(2+). One isoenzyme from rabbit lung was used to immunize a goat, and one from beef lung was used to immunize a rabbit. In immunoelectrophoresis, each resulting antiserum formed a single precipitin line with its homologous enzyme. They cross-reacted with the other three isoenzymes from the same species, but not with any isoenzyme from the other species. At high concentrations, each antiserum completely inhibited the proteolytic activity of its homologous enzyme. The antiserum against rabbit lung cathepsin D also inhibited the proteolytic activity of rabbit peritoneal and pulmonary macrophages. In limited quantities, this antiserum has now been made commercially available and is being used with labeled antibody techniques to identify under a microscope the presence of cathepsin D in macrophages and to study its role in the pathogenesis of tuberculosis.